Treatment with endoscopic transnasal resection of hypothalamic pilocytic astrocytomas: a single-center experience - Zhou, Zhuo-Ya (BMC Surg, 2021)
BACKGROUNDS: Pilocytic astrocytomas (PAs) are World Health Organization (WHO) grade I tumors, which are relatively common, and are benign lesions in children. PAs could originate from the cerebellum, optic pathways, and third ventricular/hypothalamic region. Traditional various transcranial routes are used for hypothalamic PAs (HPAs). However, there are few studies on hypothalamic PAs treated through the endoscopic endonasal approach (EEA). This study reports the preliminary experience of the investigators and results with HPAs via expanded EEAs. METHODS: All patients with HPAs, undergone EEA in our hospital from 2017 to 2019, were retrospectively reviewed. The demographic data, clinical symptoms, complications, skull base reconstruction, prognosis, and endocrinological data were all recorded and analyzed in detail. RESULTS: Finally, five female patients were enrolled. The average age of patients was 28.6 ± 14.0. All patients had complaints about their menstrual disorder. One patient had severe bilateral visual impairment. Furthermore, only one patient suffered from severe headache due to acute hydrocephalus, although there were four patients with headache or dizziness. Four cases achieved gross-total resection, and one patient achieved subtotal resection. Furthermore, there was visual improvement in one patient (case 5), and postoperative worsening of vision in one patient (case 4). However, only one patient had postoperative intracranial infection. None of the patients experienced a postoperative CSF leak, and in situ bone flap (ISBF) techniques were used for two cases for skull base repair. In particular, ISBF combined with free middle turbinate mucosal flap was used for case 5. After three years of follow-up, three patients are still alive, two patients had no neurological or visual symptoms, or tumor recurrence, and one patient had severe hypothalamic dysfunction. Unfortunately, one patient died of severe postoperative hypothalamus reaction, which presented with coma, high fever, diabetes insipidus, hypernatremia and intracranial infection. The other patient died of recurrent severe pancreatitis at one year after the operation. CONCLUSION: Although the data is still very limited and preliminary, EEA provides a direct approach to HPAs with acceptable prognosis in terms of tumor resection, endocrinological and visual outcomes. ISBF technique is safe and reliable for skull base reconstruction.